Practising Australian labour law in the new economy : Australian Labour Law Association Inaugural National Conference, 4-5 October 2002, The University of Melbourne. (The Association, 2002)
Practising Australian labour law in the new economy : papers from the inaugural conference 4-5 October, 2002 - Melbourne.